Availability of Fresh Fish Stall Business to Meet Nutritional Needs for Health: A Case Study in Sebulu District, Kutai Kartanegara Regency, Indonesia - Gusti Haqiqiansyah; Muhammad Syafril; Handayani Boa (GHMJ (Global Health Management Journal), 2026)
Background: A profitability analysis is crucial for assessing a business’s ability to generate profit hence, business actors need to respond and make the increase in managing their businesses. If their business is survived they may to meet nutritional needs of the community besides significantly contribute to increasing family income. Aims: To analyze the profitability of a fresh fish stall business. Methods: Data collection of research was in July-September 2025, in Sebulu District, Kutai Karatenagara Regency. Samples as respondents were obtained using the purposive sampling method, specifically four respondents, considering that they have the largest businesses with five and more than 5 years, and operate continuously. They are the fresh fish stall traders. To analyze profitability, calculations of Net Profit Margin (NPM), Return on Investment (RoI), Payback Period (PP), and business efficiency (RCR or Benefit Cost Ratio) were used. Results: The findings reveal that the business achieved a profitability rate of 19.10% for NPM, 29.2% for ROI, and a payback period of 0.59 years. Conclusion: The fresh fish stall business generates a relatively good profit and has the potential to sustain its operations to meet nutritional needs for health. Furthermore, the business efficiency analysis indicates an R/C ratio value of 1.24, signifying that the business is efficient, as an R/C ratio value greater than 1 denotes efficiency.